2017
DOI: 10.4067/s0718-58392017000100011
|View full text |Cite
|
Sign up to set email alerts
|

Microbial responses in a cold waterlogged paddy field to different distances from a drainage ditch

Abstract: Cold waterlogged paddy field is a type of low-yield paddy soil, and opening a drainage ditch has been suggested to improve waterlogged paddy soil and to increase the rice yield. However, little has been done on the role of a drainage ditch in ameliorating waterlogged soil. In the present study, rice (Oryza sativa L.) yield, soil physicochemical properties, microbial abundances and community structures in the surface soil of a cold waterlogged paddy field, which has three treatments with different distances fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The soil microbial communities are essential drivers in the mineralization of organic matter and mediate soil nutrient cycling [50]. Previous studies showed shifts in the soil bacterial and fungal communities with distance gradient from the ditch [9,51]. For example, Qiu et al [52] revealed that fungal diversity was higher at a plot 5 m from the ditch related to the well-drained soil condition and the improvements in nutrient availability compared to the plot at a 75 m distance with poor drainage condition.…”
Section: Absorptive Root Morphological Variation Along With the Distance From The Ditchmentioning
confidence: 99%
“…The soil microbial communities are essential drivers in the mineralization of organic matter and mediate soil nutrient cycling [50]. Previous studies showed shifts in the soil bacterial and fungal communities with distance gradient from the ditch [9,51]. For example, Qiu et al [52] revealed that fungal diversity was higher at a plot 5 m from the ditch related to the well-drained soil condition and the improvements in nutrient availability compared to the plot at a 75 m distance with poor drainage condition.…”
Section: Absorptive Root Morphological Variation Along With the Distance From The Ditchmentioning
confidence: 99%